A novel 24-slots14-poles fractional-slot concentrated winding topology with low space harmonics for electrical machines - Zhu, Shaohong; Cox, Tom; Xu, Zeyuan; Gerada, C. (2018)
This paper proposes a novel winding layout for the machines with fractional-slot concentrated windings (FSCW) using a stator shifting concept and non-overlapping windings, with which all the non-working harmonics will be completely cancelled or significantly reduced. First, the basic winding layout with a 24slot 14pole machine to reduce the significant 1st sub-harmonic will be presented for machines with single layer (SL) windings. From this, a novel double layer (DL) winding layout using the stator shifting concept will be introduced. By adopting two SL winding sets with a 105deg mechanical angle shift with respect to each other, it is not necessary to use overlapping windings. With this configuration, the 1st sub-harmonic will be completely cancelled and the parasitic 5th harmonic will be significantly reduced. Hence, the rotor losses, specifically magnet loss will be significantly reduced. Finally, two PM machines with different DL winding layout, viz., conventional 12slot 14pole and 24slot 14pole machine, will be designed and compared to validate the advantages of this winding topology.